Periodontal Referral Guidelines for Predoctoral Dental Students - Kavitha Parthasarathy; Sridhar VK Eswaran (Association of American Medical Colleges, 2013)
Abstract Teaching the basis and concept of periodontal referral at a predoctoral level can be challenging. Having well-defined guidelines for basing referral decisions provides the students with a clear objective and understanding of referral curriculum. The Periodontal Referral Guidelines resource was developed specifically to address the importance of periodontal referral in the undergraduate curriculum as well as enhance referral education in the clinics, by giving students a more simplistic approach to decision making during periodontal therapy. Incorporating clinical cases with the guidelines and an audience response system encourages interaction, participation, and gives the presenter instant feedback on student understanding. The following presentation can be used in the lecture hall. The "Guidelines for Periodontal Referral" should be presented and discussed first. The audience is then given an opportunity to apply the guidelines to clinical cases that follow. The user will need approximately 30 minutes for this presentation. Students are able to apply this knowledge at the chairside to determine further treatment options for their periodontal patients. This resource can be effectively used in the dental student and dental clinical hygiene curriculum.